Effect of Changes in Interest Rates and Exchange Rates on Stock Prices Period 2018-2019 - M. Anton Fatoni; Fransiska Simanullang (Kusuma Negara Business School, 2020)
Shares are securities in the form of proof of ownership of companies traded on a stock exchange, where the stock price is the result of an agreement between the buyer and seller. Changes in stock prices are caused by changes in the perception of each party of a stock traded, where changes in perception are caused by changes in information as a basis for investment decision making. Because there is a lot of information available on the capital market that can affect stock prices. Changes in interest rates and exchange rates (exchange rates) are also the main factors that influence investor perceptions of the results to be received which are reflected in changes in stock prices. The tendency of rising interest rates will result in the expected return on investment also going up, on the other hand there is a potential return to be received as a result of declining company performance. on stock prices on the Indonesia Stock Exchange (BEI) and want to know the extent of the influence of changes in interest rates and the exchange rate of Rupiah / USD. on stock prices on the Indonesia Stock Exchange (BEI) Period 2018 - 2019.